The effect of conductive fillers and poly (ethylene glycol) diglycidyl ether on the properties of poly (vinyl chloride)/poly (ethylene oxide) conductive films - Siti Hajar Mohd Din (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
In this research, the conductive films based on poly (vinyl chloride)/poly (ethylene oxide) (PVC/PEO) with conductive fillers like carbon black, polyaniline and polypyrrole were prepared by solution casting method at the speed of 400 rpm. The composition of 5, 10, 15, 20, 25, 30 wt % of filler loading were incorporated in PVC/PEO: 50/50 blends. The tensile properties, morphology, Fourier Transform Infrared spectroscopy (FTIR) analysis, electrical conductivity and thermogravimetric analysis (TGA) were studied. Poly (vinyl chloride)/poly (ethylene oxide)/carbon black (PVC/PEO/CB) at different compositions were prepared. The tensile strength and modulus of elasticity were increased until up to 25 wt% with the addition of the CB by 25.33% and 16.66% respectively.